ARTIFICIAL INTELLIGENCE IN THE SYSTEM OF QUESTIONS «DIGIGRAM FOR TEACHERS» - Marienko, Maiia (Physical and Mathematical Education, 2024)
Formulation of the problem. In 2024, the Institute for Digitalisation of Education of the National Academy of Educational Science of Ukraine launched the study "Design and Use of an Open Educational Environment with Elements of Artificial Intelligence for the Professional Development of Teaching Staff." One of the possible options for researching the state of the problem is the analysis of the system of questions of the national test "Digigram for teachers." The content of such questions and their number will allow us to analyze how teachers use this or that service, their distribution, and their knowledge about artificial intelligence.Materials and methods. Systematic analysis of pedagogical and general scientific sources to clarify the state of development of the problem of using artificial intelligence in the field of education (Ukrainian and foreign experience); analysis of pedagogical, scientific literature to identify the main principles of building a system of questions of the national test "Digigram for teachers"; a comparative analysis to determine the most critical thematic blocks in the "Digigram for teachers" test.Results. The analysis of the system of questions "Digigram for teachers" led to the formation of the primary author's thematic blocks by which all available questions can be divided: Facebook, Google Applications, YouTube, Electronic government, Electronic school, Working with a browser, Windows operating system, Inclusive education. Each block contains relevant components that characterize it in its entirety. The thematic block "Google Applications," which includes specific issues in the field of artificial intelligence, consists of the following services: Google Docs, Google Sheets, Google Presentations, Google Forms, Google Sites, Google Classroom, Google Drive, Google Maps, and Google Images.Conclusions. In the "Digitgram for Teachers" test, only a few questions are related to artificial intelligence. No direct questions were identified that would highlight the use of artificial intelligence services in the educational process. In passing, specific questions can be related to using artificial intelligence (for example, those associated with Google Image or Google Maps services). Only 2% of such questions were found (1 out of 61 or 62). Their number will not help during the ascertainment stage of the pedagogical experiment, which is planned for 2024. The following steps will be to create methods and guidelines for using AI in the educational process.
Keywords: Artificial Intelligence; Digigram for teachers; system of questions; teachers; teaching staff; AI